A Comprehensive Review on Solid Lipid Nanoparticle Using Herbal Plant Extract - Adhikari, Himanshu; Bhardwaj, Manoj; Bisht, Manoj; Rawat, Shalini (Journal of Neonatal Surgery, 2025)
Drug delivery systems have seen a revolution because to nanotechnology, which provides precise, regulated, and targeted treatment solutions with the fewest possible negative effects. This study examines several nanocarriers that are essential for improving medication efficacy, such as dendrimers, liposomes, solid lipid nanoparticles (SLNs), nanoparticles, nanosuspensions, and polymeric nanoparticles. SLNs provide a better option than the others because of their physiological lipid content, which reduces toxicity and maximizes medication absorption. Solvent evaporation, emulsification-diffusion, polymerization, and ultrasonication are some of the preparation techniques that guarantee the structural soundness and functional effectiveness of SLNs. Their flexibility in pharmaceuticals is demonstrated by their broad variety of uses, which include oral, parenteral, transdermal, topical, and cosmetic formulations. Additionally, extracts from ashwagandha, eugenol, neem, aloe vera, and curcumin have been shown to have improved bioavailability and therapeutic efficacy in herbal-loaded SLNs, especially in anti-inflammatory, antibacterial, antioxidant, and anti-tumor therapies. The stability and effectiveness of SLN are continuously being improved by formulation technology innovations, despite obstacles such burst drug release and fast systemic clearance. This research demonstrates the enormous potential of medication delivery powered by nanotechnology in improving contemporary medical treatments and offering creative ways for improved therapeutic results